2011
DOI: 10.1074/jbc.m110.166256
|View full text |Cite
|
Sign up to set email alerts
|

A Two-step Mechanism for the Folding of Actin by the Yeast Cytosolic Chaperonin

Abstract: Actin requires the chaperonin containing TCP1 (CCT), a hexadecameric ATPase essential for cell viability in eukaryotes, to fold to its native state. Following binding of unfolded actin to CCT, the cavity of the chaperone closes and actin is folded and released in an ATP-dependent folding cycle. In yeast, CCT forms a ternary complex with the phosducin-like protein PLP2p to fold actin, and together they can return nascent or chemically denatured actin to its native state in a pure in vitro folding assay. The com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 23 publications
4
38
0
Order By: Relevance
“…However, because of the absence of antibody labelling data on closed CCT complexes, it is not known formally if actin's so‐called subdomain 2 disengages from Cct4 in the closed state as implied in the early model of the closed state of the CCT–actin complex (Llorca et al , 2001b). We now consider that more complex reconfigurations of the partially folded actin molecule on the apical domain surfaces can occur upon lid‐closure, based upon protease‐protection mapping experiments with yeast CCT–ACT1sub4–PLP2 complexes (McCormack et al , 2009) and spectroscopic analysis of CCT–ACT1–PLP2 folding kinetics (Stuart et al , 2011). The X‐ray structure shown here with its novel interactions between actin and Cct1 and Cct7 supports the model of more complex reconfigurations occurring during the two‐step folding cycle (Stuart et al , 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, because of the absence of antibody labelling data on closed CCT complexes, it is not known formally if actin's so‐called subdomain 2 disengages from Cct4 in the closed state as implied in the early model of the closed state of the CCT–actin complex (Llorca et al , 2001b). We now consider that more complex reconfigurations of the partially folded actin molecule on the apical domain surfaces can occur upon lid‐closure, based upon protease‐protection mapping experiments with yeast CCT–ACT1sub4–PLP2 complexes (McCormack et al , 2009) and spectroscopic analysis of CCT–ACT1–PLP2 folding kinetics (Stuart et al , 2011). The X‐ray structure shown here with its novel interactions between actin and Cct1 and Cct7 supports the model of more complex reconfigurations occurring during the two‐step folding cycle (Stuart et al , 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies using archaeal and eukaryotic chaperonins have suggested that ATP binding suffices to close the built-in lid and trigger substrate folding (Iizuka et al, 2003; Llorca et al, 2001; Villebeck et al, 2007; Stuart et al, 2010). Subsequent ATP hydrolysis would serve to reopen the lid and release the folded protein.…”
Section: Introductionmentioning
confidence: 99%
“…The current model proposes that group II chaperonins do not release the substrate during folding (Gómez-Puertas et al, 2004; Stuart et al, 2010). Instead, ATP binding would cause the apical domains with their bound substrate to move, and this movement mechanically forces substrate folding.…”
Section: Introductionmentioning
confidence: 99%
“…Steady progress continues to be made on the structure-function relationships and reaction cycles of chaperones bound to individual client proteins [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. In this issue, however, we return to first principles, and shine the spotlight on the role of chaperones in biomolecular assemblies, as first defined for nucleosomes by Laskey [17].…”
Section: Chaperones At the Crossroads Of Life And Deathmentioning
confidence: 99%